A 3D analytical model to investigate laser-induced shock wave generation in water - Saeed Ghahramani, Mohammad; Khalilzadeh, Javad (Optics and laser technology, 2025)
•Presented model analyzes the shock wave resulting from the laser plasma when the nanosecond laser interacts with water.•Simulation the properties of the mechanical wave, including the shock wave emission time from the wall of the plasma sphere, the initial pressure and frequency of the shock wave.•Verified the presented model by an experimental shadow-graphic experiment. Photoacoustic phenomenon offers an efficient means of generating sound pulses. The interaction of laser and plasma is a very crucial subject in the study of the photoacoustic phenomenon. However, existing researches based on the plasma sphere approach, often neglect this interaction, treating the sound wave as a simple output from the plasma. This paper presents a model for analyzing the shock wave resulting from the laser plasma when the nanosecond laser interacts with water. The model calculates key mechanical wave properties, including the shock wave emission time from the the plasma sphere boundary, the initial pressure of the shock wave, and the wave frequency, based on the characteristics of the created plasma. According to the investigations, a laser with a power density of 6 GW.cm−2 creates a shock wave with an initial pressure of 4.3 MPa and 4520 kHz frequency.